2014
DOI: 10.1002/ange.201407783
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Gold Nanoparticles in Enhancing the Catalytic Activity of Manganese Oxides in Water Oxidation Reactions

Abstract: The Earth‐abundant and inexpensive manganese oxides (MnOx) have emerged as an intriguing type of catalysts for the water oxidation reaction. However, the overall turnover frequencies of MnOx catalysts are still much lower than that of nanostructured IrO2 and RuO2 catalysts. Herein, we demonstrate that doping MnOx polymorphs with gold nanoparticles (AuNPs) can result in a strong enhancement of catalytic activity for the water oxidation reaction. It is observed that, for the first time, the catalytic activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 42 publications
1
28
3
Order By: Relevance
“…-The role of redox-active supports combined with Mn oxides toward water oxidation is complex. For the catalyst reported here and in the presence of Ce(IV), gold shows a lower effect than in the previously reported gold-doped catalysts (Najafpour et al 2013e;Gorlin et al 2014;Kuo et al 2014). We propose that the true role of gold in these catalysts depends on the methods of synthesis and the effect should be studied more carefully.…”
Section: Water Oxidationcontrasting
confidence: 54%
See 4 more Smart Citations
“…-The role of redox-active supports combined with Mn oxides toward water oxidation is complex. For the catalyst reported here and in the presence of Ce(IV), gold shows a lower effect than in the previously reported gold-doped catalysts (Najafpour et al 2013e;Gorlin et al 2014;Kuo et al 2014). We propose that the true role of gold in these catalysts depends on the methods of synthesis and the effect should be studied more carefully.…”
Section: Water Oxidationcontrasting
confidence: 54%
“…Gold nanoparticles are more active toward KMnO 4 reduction than the bulk substance: Subbaraman et al reported that water oxidation of four first-row transition metal oxides did not vary with the nature of the metal support (Subbaraman et al 2012), other groups reported the importance of supports for the first-row transition metal oxides in water oxidation (El-Deab et al 2007;Mohammad et al 2008;Najafpour et al 2013e;Gorlin et al 2014;Kuo et al 2014;Bell 2011, 2012). In the Photosynth Res previous study (Najafpour et al 2013e), the gold nanoparticles deposited on layered Mn oxide were reported.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations